A Study on the Power Line Operation Strategy by the Energy Storage System to Ensure Hosting Capacity of Distribution Feeder with Electrical Vehicle Charging Infrastructure - Byungki Kim (MDPI AG, 2021)
The introduction of a complex electrical vehicle charging (EVC) infrastructure consisting of an electrical vehicle (EV) charger and renewable energy source (RES) in the distribution system has been required as an important countermeasure for global environmental issues. However, the problems for hosting capacity and power stability of the distribution feeder can be caused by the penetration of lager scaled RES and EVC infrastructure. Further, it is required for the efficient operation method to prevent congestion and to ensure hosting capacity for the distribution feeder due to the increase of variable RES and EVC infrastructure in the distribution systems. In order to solve these problems, it is necessary to develop a technology which is capable of stably introducing an EVC infrastructure without reinforcing the existing distribution system. Therefore, to maintain the existing hosting capacity of distribution feeder and allowable limits, this paper presents a virtual power line (VPL) operation method using Energy Storage System (ESS) based on the power and voltage stabilization control to ensure hosting capacity of the EVS infrastructure. The proposed operation method is determined by optimal power compensation rate (PCR) and voltage compensation rate (VCR). Specifically, ESS for VPL is controlled according to the charging and discharging mode is operated according to the comparison value of the PCR and VCR. From the test results, it is verified that hosting capacity of the distribution system can be maintained using the proposed control method of ESS for VPL operation.